SARS‐CoV‐2, SARS‐CoV, and MERS‐CoV encode circular RNAs of spliceosome‐independent origin. Issue 7 (31st March 2022) - Yang, Shaomin; Zhou, Hong; Liu, Mingde; Jaijyan, Dabbu; Cruz‐Cosme, Ruth; Ramasamy, Santhamani; Subbian, Selvakumar; Liu, Dongxiao; Xu, Jiayu; Niu, Xiaoyu; Li, Yaolan; Xiao, Lizu; et al.
Abstract: Circular RNAs (circRNAs) are a newly recognized component of the transcriptome with critical roles in autoimmune diseases and viral pathogenesis. To address the importance of circRNA in RNA viral transcriptome, we systematically identified and characterized circRNAs encoded by the RNA genomes of betacoronaviruses using both bioinformatical and experimental approaches. We predicted 351, 224, and 2764 circRNAs derived from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), SARS‐CoV, and Middle East respiratory syndrome coronavirus, respectively. We experimentally identified 75 potential SARS‐CoV‐2 circRNAs from RNA samples extracted from SARS‐CoV‐2‐infected Vero E6 cells. A systematic comparison of viral and host circRNA features, including abundance, strand preference, length distribution, circular exon numbers, and breakpoint sequences, demonstrated that coronavirus‐derived circRNAs had a spliceosome‐independent origin. We further showed that back‐splice junctions (BSJs) captured by inverse reverse‐transcription polymerase chain reaction have different level of resistance to RNase R. Through northern blotting with a BSJ‐spanning probe targeting N gene, we identified three RNase R‐resistant bands that represent SARS‐CoV‐2 circRNAs that are detected cytoplasmic by single‐molecule and amplified fluorescence in situ hybridization assays. Lastly, analyses of 169 sequenced BSJs showed that both back‐splice and forward‐splice junctions were flanked by homologous and reverse complementary sequences, including but not limited to the canonical transcriptional regulatory sequences. Our findings highlight circRNAs as an important component of the coronavirus transcriptome, offer important evaluation of bioinformatic tools in the analysis of circRNAs from an RNA genome, and shed light on the mechanism of discontinuous RNA synthesis.